Pilot exploration of the association between self-esteem and professional satisfaction in Hellenic Hospital nurses - Papathanassoglou, Elizabeth; Giannakopoulou, Margarita; Koutroubas, Anna; Karanikola, Maria (My University, 2007)
Aim To explore potential associations between nurses' self-esteem and professional satisfaction. Background Professional burnout and moderate job satisfaction have been reported consistently among nurses. However, potential associations of the above elements with personality characteristics have not been adequately addressed. Methods A random sample of 154 adult healthcare nurses completed the Maslach Burnout Inventory, the Berger's Scale and the Index of Work Satisfaction. Associations and comparisons across different settings and background variables were explored. Results Moderate to positive levels of self-acceptance (mean Likert rating: 3.95 ± 0.51) and acceptance-of-others (mean Likert rating: 3.7 ± 0.43) and low to moderate levels of professional satisfaction (mean Likert rating: 3.69 ± 0.63) were observed. Positive correlations were detected between professional satisfaction and self-esteem indices (r = 0.249–0.313, P ≤ 0.008). A mediating effect of burnout was implied. Conclusions A potential interaction between personality and professional attitudes of Hellenic Hospital nurses was observed. The present study is limited within the correlational frame. Further study is needed to investigate a potential causal relationship between self-esteem indices and professional satisfaction, in order to inform nursing retention and support policies.
Keywords: Burnout; Hellenic; Job satisfaction; Nursing; Self-acceptance